2007
DOI: 10.1098/rspa.2007.1848
|View full text |Cite
|
Sign up to set email alerts
|

An extended Reynolds analogy for excited wavy instabilities of developing streamwise vortices with applications to scalar mixing intensification

Abstract: Studies are presented to elucidate the role of steady streamwise vortex structures, initiated upstream from weak Görtler vortices in the absence of explicit vortex generators, and their excited nonlinear wavy instabilities in the intensification of scalar mixing in a spatially developing mixing region. While steady streamwise vortex flow gives rise to significant mixing enhancement, the excited nonlinear wavy instabilities, which in turn modify the basic three-dimensional streamwise vortices, give rise to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 68 publications
0
14
0
Order By: Relevance
“…Through the effects of eddy heat and mass flux from secondary instability, significant enhancement of momentum and scalar mixing has been found possible in free mixing layers (Girgis & Liu 2002;Liu 2007). It is anticipated that much more complex fluid properties and geometry would have to be taken into consideration of intensifying mixing in practical combustors and in jet exhausts in a well-controlled manner for minimizing pollutants of combustion and of aerodynamic sound.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the effects of eddy heat and mass flux from secondary instability, significant enhancement of momentum and scalar mixing has been found possible in free mixing layers (Girgis & Liu 2002;Liu 2007). It is anticipated that much more complex fluid properties and geometry would have to be taken into consideration of intensifying mixing in practical combustors and in jet exhausts in a well-controlled manner for minimizing pollutants of combustion and of aerodynamic sound.…”
Section: Discussionmentioning
confidence: 99%
“…This reduces to arguing for similarity between (2.8) and (2.11), leading to u 0 Zq 0 . The author (Liu 2005(Liu , 2007 has shown that the pressure gradient term in (2.8), which is the impediment to similarity, is of the order of the magnitude of u 0 /1 relative to the inertia terms. In this case, (2.8) is similar to (2.11), and, for PrZ1 and similar initial and boundary conditions, the Reynolds analogy follows:…”
Section: An Extended Reynolds Analogymentioning
confidence: 99%
See 1 more Smart Citation
“…9 The passive scalar iso-lines are similar to the velocity structures for Prandtl and Schmidt numbers near unity in the mixing region supporting steady streamwise vortices and their nonlinear secondary instabilities. 22
Figure 1.The flow is from left to right. Local cross sectional plane “streamlines” and iso-u contour “mushrooms”.
…”
Section: Steady Streamwise Vorticity and Excitation Of Secondary Instmentioning
confidence: 99%
“…10 Iso-u contour “mushrooms” are also that of iso-scalars contours (dimensionless temperature and concentration for a binary mixture) for Prandtl and Schmidt numbers unity. 11 …”
Section: Steady Streamwise Vorticity and Excitation Of Secondary Instmentioning
confidence: 99%